Komposisi Arthropoda di Pertanaman Padi Sistem Legowo 2:1 dan Legowo 4: - Fatahuddin Fatahuddin; Itji Diana Daud; Sri Nur Aminah (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2020)
Fatahuddin F, Daud, ID, Aminah, SN. 2020. The arthropods composition in rice cropping system logowo 2:1 and legowo 4:1. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Legowo methods is a rice planting between two or more rows of rice plant and one empty row. The research objectives is to determine composition of arthropods in rice planting system Legowo 2:1 and Legowo 4:1. The research was held at farmer rice plantation in North Polongbangkeng, Takalar Regency, South Sulawesi from May to August 2019. Arthropods in Legowo 2:1 and Legowo 4:1 captured by suction of Dvac pump when rice plants age 21 to 84 days after planting (DAP), an observation interval of 7 days. The arthropods from Dvac suction were identified at Pest Laboratory, Department of Plant Pests and Diseases, Faculty of Agriculture, Hasanuddin University. The results showed rice plant in Legowo 2:1, the highest arthropods population was found at 56 DAP (13 individuals) and lowest predator population at 21 DAP (1 individual). The types of arthropods found from group of spiders and insects. The highest predatory population in rice cultivation with Legowo 4:1 found at 56 DAP (22 individual), and lowest population at 21 DAP (5 individual). The composition of parasitoid insects found in Legowo 2:1 at 49 DAP about 4 individuals. The highest parasitoid insect population in Legowo 4:1 was found at 77 DAP (6 individuals), then lowest population at 21 DAP (1 individual). The conclusion of research is: the types of predators found in Legowo 2:1 and Legowo 4:1 from the orders of Aranea, Coleoptera, Odonata and Orthoptera. The parasitoids found in the Legowo 2:1 and Legowo 4:1 were from the order Diptera and Hymenoptera.